Biochemical Cardiac Markers in Clinical Cardiology (Journal of Medicine, 2009)
Millions of patients present annually with chest pain, but only 10% to 15% have myocardial infarction. Lack of diagnostic sensitivity and specificity of clinical and conventional markers prevents or delays treatment and leads to unnecessary costly admissions. Comparative data are lacking on the new markers, yet using all of them is inappropriate and expensive. The biochemical marker determination to clinical cardiology and discusses some important developments in this field. Biochemical markers play a pivotal role in the diagnosis and management of patients with acute coronary syndrome (ACS), as witnessed by the incorporation of cardiac troponins into new international guidelines for patients with ACS and in the redefinition of myocardial infarction. Despite the success of cardiac troponins, there is still a need for the development of early markers that can reliably rule out ACS from the emergency room at presentation and also detect myocardial ischaemia in the absence of irreversible myocyte injury. The cardiac natriuretic peptides, Laboratory Medicine are also assuming a role in the assessment of cardiac function. Biochemical markers now play an important role in the detection of disease, risk stratification and the monitoring of therapy. Keywords: Biochemical markers, Myocardial infarction, Troponin, Brain natriuretic peptide   doi: 10.3329/jom.v10i2.2824   J MEDICINE 2009; 10 : 100-108